Text classification with Naïve Bayes - Yew, Yap Chi; Cheng, Tan Guan; Sen, Derric Chong Wei; Wei, Bee Jian; Salam, Zailan Arabee Abdul (Journal of Applied Technology and Innovation, 2021)
Naive Bayes is an algorithm which is swift and easy to apply and always used in text classification. In this paper, we anchor in the performance of Naive Bayes text classifiers with a couple of datasets. We have modified the code to measure the accuracy of the algorithm in predicting words. We also use an interactive graph to show the prediction of the algorithm. We found out that Naive Bayes can provide uncomplicated probabilistic predictions which are very smoothly interpretable with only a few tuneable parameters.